The Use of Japanese Loanwords in Culinary Content on Instagram - Rasiban, Linna Meilia; Rahmayanti, Amalia; Renariah, Renariah; Sutedi, Dedi (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2021)
The purpose of this study is to examine the phenomenon of Japanese loanwords (gairaigo) used in culinary content on Instagram, and to describe the analytical framework of those meaning and formation. This study used descriptive qualitative method with data sources from 8 Instagram accounts of culinary content. This data in this study including 74 postings and 115 data of loanwords use from the Instagram accounts. The results from this study showed that lexical and word-formation structure that form the Japanese loanwords mostly were the compound word form (fukugougo) because many cuisine terms used two or more words. The results also showed that many of Japanese loanwords in culinary content are using derivative forms and acronyms. It is suggested that teachers and Japanese learners should be aware of these structure changes and semantic change in Japanese loanwords, which can help Japanese learners to understand the meaning of loanwords in Japanese.